Dual network poly(dimethyl siloxane)–impact hardening polymer composite with autonomous self-healing and soft–stiffness switch abilities. (December 2022) - Liu, Ying; Zhou, Chao; Lv, Junping; Bai, Yungang; Xu, Kun; Zhang, Hao; Huang, Xiaona; Wang, Chao; Zhang, Fan; Wang, XinYue; Wang, Jiarui; Jiang, Hang; et al.
Abstract: Smart protection materials have been widely used in personal and military fields. In this scheme, a series of poly(dimethyl siloxane) (PDMS)–impact hardening polymer (IHP) composite elastomers, with self-healing abilities and soft–stiffness switch abilities, were fabricated. PDMS, a flexible polymer with excellent mechanical properties, can function as a trestle, helping maintain the shape of the IHP, while the IHP can absorb and dissipate the impact energy to play a protective role. Under the joint action of PDMS and IHP, the fracture toughness of PDMS–IHP increased from 359 % to 464 % as the strain rate increased from 10 to 400 mm min -1, whereas that of the unmodified PDMS elastomer decreased from 392 % to 120 % within the same strain rate range. Furthermore, the impact energy absorption efficiency of PDMS–IHP increased to 85.97 % at an impact speed of 4.43 m s -1, showing excellent performance in the protection of impact. In addition, PDMS–IHP showed good self-healing ability, with a toughness healing efficiency of 83.09 % within 48 h. These excellent properties make PDMS–IHP composite candidates suitable for applications in both emerging and well-developed fields. Graphical Abstract: ga1